2017
DOI: 10.3390/ijms18112482
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Neurological Diseases: An Endocrine View

Abstract: Vitamin D system comprises hormone precursors, active metabolites, carriers, enzymes, and receptors involved in genomic and non-genomic effects. In addition to classical bone-related effects, this system has also been shown to activate multiple molecular mediators and elicit many physiological functions. In vitro and in vivo studies have, in fact, increasingly focused on the “non-calcemic” actions of vitamin D, which are associated with the maintenance of glucose homeostasis, cardiovascular morbidity, autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
97
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(108 citation statements)
references
References 266 publications
(339 reference statements)
1
97
0
10
Order By: Relevance
“…Chronic exposure to alcohol has the potential to reduce the levels of vitamin D. 34 Several evidence suggests that vitamin D acts like a neurosteroid and is required for normal brain development and function. 35 An endocrine review on Vitamin D and neurological diseases, aimed to highlight the relationship between vitamin D and neurological diseases stated that there is association between low levels of 25(OH)D and a wide spectrum of neurodegenerative conditions such as multiple sclerosis, Alzheimer's disease, Parkinsons's disease and neurocognitive disorders, is supported by in vitro and in vivo data. 35 Other studies showed that the risk of MS decreases with increasing intake of vitamin D 36 , and serum 25(OH)D levels are signi cantly lower in patients with MS as compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic exposure to alcohol has the potential to reduce the levels of vitamin D. 34 Several evidence suggests that vitamin D acts like a neurosteroid and is required for normal brain development and function. 35 An endocrine review on Vitamin D and neurological diseases, aimed to highlight the relationship between vitamin D and neurological diseases stated that there is association between low levels of 25(OH)D and a wide spectrum of neurodegenerative conditions such as multiple sclerosis, Alzheimer's disease, Parkinsons's disease and neurocognitive disorders, is supported by in vitro and in vivo data. 35 Other studies showed that the risk of MS decreases with increasing intake of vitamin D 36 , and serum 25(OH)D levels are signi cantly lower in patients with MS as compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The vitamin D receptor, as well as 1‐alpha hydroxylase, the enzyme that converts vitamin D to its active form (1, 25‐dihydroxyvitamin D (25(OH)D)), are found in the brain, with 1‐alpha hydroxylase seen in the hippocampus which is important for memory . Vitamin D is neuroprotective, promoting amyloid metabolism and clearance in the brain, neuronal and synaptic growth, and neurotransmission . Thus, it would seem logical that there is a link between hypovitaminosis D and dementia .…”
mentioning
confidence: 99%
“…9 Vitamin D is neuroprotective, promoting amyloid metabolism and clearance in the brain, neuronal and synaptic growth, and neurotransmission. 10 Thus, it would seem logical that there is a link between hypovitaminosis D and dementia. 11 A previous study found that elderly adults with vitamin D deficiency (<10 ng/mL) had cognitive decline based on Mini-Mental State Examination (MMSE) results over 6 years.…”
mentioning
confidence: 99%
“…Although effective in some cases, adverse effects of this therapy are widely reported (Sohrabji and Bake, 2006), therefore, it is very important the search for alternative and/or complementary therapies in order to ameliorate the general health of women in the postmenopausal period. In this context, vitamin D (VIT D) has been considered a steroid hormone beneficial for calcium homeostasis with antioxidant and anti‐inflammatory activities (Di Somma et al, 2017; Hajiluian et al, 2017; Longoni et al, 2017). In humans, the main sources of VIT D are endogenous production (Barberger‐Gateau, 2014; Di Somma et al, 2017; Mpandzou et al, 2016; Stroud et al, 2008) or diet, which has become an important alternative source of this vitamin.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, vitamin D (VIT D) has been considered a steroid hormone beneficial for calcium homeostasis with antioxidant and anti‐inflammatory activities (Di Somma et al, 2017; Hajiluian et al, 2017; Longoni et al, 2017). In humans, the main sources of VIT D are endogenous production (Barberger‐Gateau, 2014; Di Somma et al, 2017; Mpandzou et al, 2016; Stroud et al, 2008) or diet, which has become an important alternative source of this vitamin. Studies have already shown some benefits of different doses of VIT D supplementation on OVX effects on the body weight gain, lipid profiles, visceral fat and waist circumference (Babaei et al, 2017), articular cartilage erosion by regulating collagen II turnover through TGF‐beta1 (Li et al, 2016), as well as hippocampal cytoskeleton imbalance (Siebert et al, 2017).…”
Section: Introductionmentioning
confidence: 99%